Bridging the gap between prisons and society; revisiting mental health, addiction, and education - Eleni Beri; Anna Mizzi; Kamilla Bugya (Formare)
This paper explores the complexities of the penitentiary system, focusing on the mental health of inmates and ex-inmates both within prison settings and in society, as well as the societal stigma that follows their mental state. It focuses on Italy, Cyprus, Malta, and Hungary, with occasional comparisons for optimal comprehension. Additionally, the article challenges traditional views on crime, punishment, and societal reintegration, advocating for a balanced approach, combining both humanistic and behaviouristic methods, for effective rehabilitation. Another issue that is tackled is substance use inside the prison settings, addiction treatment, the cultural background that affects these attitudes and the encouragement of further education for better prevention. Finally, the subject of education inside prison settings is being discussed, which affects critically the nature and goals of the penitentiary system. Current practices are reviewed and a vision that includes enhanced education, reduced societal stigma, and evolved mental health care in the penitentiary system is presented.